Jangan Wariskan Sampah: Studi Pengelolaan Sampah Berbasis Komunitas Dalam Mencegah Dampak Lingkungan Antargenerasi - Gunawan, Muhammad Ali; Ahmad, Faraqna Algadavi Aulia; Intsi, Doa Eltazkia; Hidayatullah, Miftahul; Umam, M. Khoirul; Maulana, Hadi Syekh; Dhihriya, Asna; Falah, M. Fajurul; Safila, Ardian Yega; Romdhonah, Noviyatul; Huda, Miftakhul; Janah, Riadlotul; Handayani, Puri; Rachmawati, Diana; Ishomuddin, Muhammad (Jurnal Pengabdian Kepada Masyarakat, 2026)
This study aims to analyze community-based waste management in preventing intergenerational environmental impacts in Jenarsari Village. A qualitative approach with a case study design was used to explore the dynamics of community participation and the sustainability of waste management practices at the local level. Data were obtained through observation, semi-structured interviews, and limited questionnaires, then analyzed using an interactive model through reduction, presentation, and conclusion drawing. The results show that the formation of collective awareness, support from local leadership, and consistent outreach are the main factors in encouraging changes in community behavior. Scientific findings indicate a transformation in values ​​​​regarding waste as a resource with social and economic value. Active community participation has been shown to strengthen sorting practices and gradually reduce household residues. Furthermore, the involvement of the younger generation shows the potential for environmental sustainability in the context of intergenerational inheritance. Overall, this study confirms that community-based waste management is an effective socio-ecological strategy in building a sustainable culture of environmental awareness.